The Role of Fashion Bloggers in Fashion Marketing Communication - Mickevičiūtė, Akvilė; Siudikienė, Daiva (Information & Media, 2019)
Because of digitization and internet development that took place in the 21st century, fashion industry has been consistently encountering various challenges. While the popularity of social media continues to grow, a new player in fashion industry, along with the medium they control, has emerged – the fashion blogger and the fashion blog. After gaining millions of followers on social media, bloggers acquired a certain power position – they can influence the opinion of their audience. With the popularity of social media, fashion bloggers, who gain a certain position of power through the acquisition of large numbers of followers across social networks, can shape their followers’ opinions, present a variety of fashion product reviews, and participate in the consumer decision-making processes. For fashion companies, collaborations with bloggers are becoming more relevant and an increasing part of a fashion brand marketing strategy. This article introduces theoretical and empirical research that was carried out to analyze and explore the role of fashion bloggers in modern fashion marketing communication. Fashion companies seek to exploit this advantage for commercial purposes and include blogs as advertising channels into their marketing strategy. This article aims to analyze the role of blogs in the modern fashion industry. In order to reach that, the following objectives were set: to research the attributes of the fashion industry and fashion marketing in the 21st century; to analyze the definition, features, types, and significance of fashion blogs with reference to the current fashion industry; to examine the aspects of connection forming between fashion blogger and its audience; to explore the features of Lithuania’s fashion bloggers’ activities and the strategies they use to develop their ties with significant target audiences of the fashion sector. In order to reach the aim of research, two empirical research methods were combined: semi-structured interviews with fashion bloggers and a questionnaire for the followers of fashion blogs. During the study it was established that the role of Lithuania’s fashion blogs is best seen in fashion marketing – blogs are the mediators between fashion companies and consumers. They form a personal bond with consumers and organically disseminate fashion trends to a wide audience.
Keywords: blog; blogger; fashion industry; marketing; opinion leader; fashion influencer; social media